A CONCURRENT MD-FE COUPLING METHOD TOWARDS SIMULATIONS OF FRACTURE OF THERMOPLASTIC POLYMERS - Zhao, Wuyang; Pfaller, Sebastian (COMPLAS 2021 - 16th International Conference on Computational Plasticity: Fundamentals and Applications, 2021)
In this contribution we present a multiscale partitioned-domain method to simulate fracture of amorphous thermoplastic polymers. This method couples a particle-domain treated by the molecular dynamics (MD) framework and a continuum domain discretized by the Finite Element (FE) method. The FE domain is described by a viscoelastic-viscoplastic constitutive model that can reproduce the rate-dependent mechanical behavior of the MD domain within a moderate deformation range. In the highly deformed MD domain near the crack tip, hybrid boundary conditions are applied to mimic the plane strain condition, where the surfaces in the X-Y plane are subjected to periodic boundary conditions while non-periodic stochastic boundary conditions are used for the other surfaces. Using this method, we implement multiscale simulations of polymers with different pre-cracks and different strain rates under Mode-I loading conditions to demonstrate its capability for the investigation of polymer fracture.
CRIS-Team Scopus Importer:2024-12-16
Keywords: MD-FE coupling; Multiscale simulations; Polymer fracture; Thermoplastic polymers; viscoplasticity